Kinetics of the absorption of carbon dioxide into aqueous ammonia solutions. Issue 10 (22nd June 2016) - Yu, Hesheng; Tan, Zhongchao; Thé, Jesse; Feng, Xianshe; Croiset, Eric; Anderson, William A.
Abstract : Experiments were performed in a customized double stirred tank reactor to study the kinetics of CO2 absorption into NH3 solutions at concentrations ranging from 0.42 to 7.67 kmol·m −3 and temperatures between 273.15 and 293.15 K. The results show that the reactive absorption was first order with respect to CO2 but fractional order (1.6–1.8) with respect to ammonia. Experimental data can be satisfactorily interpreted by a termolecular mechanism using k NH 3 T = 7.6089 × 10 8 exp ⁡ ( − 4018.4 T ) and k H 2 O T = 7.9161 × 10 7 exp ⁡ ( − 4356.4 T ) . © 2016 American Institute of Chemical Engineers AIChE J, 62: 3673–3684, 2016